Optimal power dispatch for day-ahead power system operation considering demand elasticity - Kaikrathok, Pansa; Chayakulkheeree, Keerati (Institute of Advanced Engineering and Science, 2023)
This paper proposes the optimal power dispatch (OPD) considering price-based demand response (PDR). In the proposed framework, the nodal spot price (NSP) is use as a price signal to the consumers. In the proposed method, the optimal real power dispatch is solved by quadratic programming (QP) to minimize the total operating cost and obtain the NSP components. Consequently, demand elasticity (DE) is applied to estimate the system demand for more accurate day-ahead operations. In the DE matrix, the self-DEs represent the consumer consumption of hour h in response to the NSP of that hour. Meanwhile, the cross-DEs represent the response of consumer consumption of hour h to the NSP of other hours. The algorithm was tested with the IEEE 30-bus system with several cases of demand elasticity. The results show that the proposed algorithm can incorporate price elasticity of demand into day-ahead scheduling and effectively minimize total operating costs. The simulation study shown that, the operating cost can be reduced by 0.33-0.695% with self-DE of -0.1 -0.2, by reducing the consumption respected to the NSP. Meanwhile, when applying cross-DE, the operating cost can be reduced by 0.015% under the same daily consumption with the consumer’s load shifting respected to NSP.